2020
DOI: 10.1016/j.ijid.2020.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of phenotypic and genotypic antibiotic susceptibility patterns in Mycobacterium avium complex

Abstract: Phenotypic (Sensititre Myco, pDST) and genotypic drug susceptibility testing (GenoType NTM DR, gDST) in M. avium complex (MAC) have become available as standardized assays, but comparable data is needed. This study aimed to investigate the phenotypic and genotypic drug susceptibility patterns in MAC clinical isolates. Methods: Overall, 98 isolates from 85 patients were included. pDST and gDST were performed on all isolates and results compared regarding specificity and sensitivity using pDST as a reference me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…Our antibiotic susceptibility testing results supported the current recommendation of using macrolides, rifamycins, and aminoglycosides to treat MAC infections. In our study, clarithromycin showed good inhibitory activity against all MAC isolates, consistent with previous studies [19,20]. The resistance rate of MAC isolates against rifampin was 82.9% (92/111), which was in agreement (78.9%; 216/274) with a previous study [21].…”
Section: Discussionsupporting
confidence: 92%
“…Our antibiotic susceptibility testing results supported the current recommendation of using macrolides, rifamycins, and aminoglycosides to treat MAC infections. In our study, clarithromycin showed good inhibitory activity against all MAC isolates, consistent with previous studies [19,20]. The resistance rate of MAC isolates against rifampin was 82.9% (92/111), which was in agreement (78.9%; 216/274) with a previous study [21].…”
Section: Discussionsupporting
confidence: 92%
“…These differences could be related to the prevailing susceptibility pattern of M. kansasii isolates found in a particular geographical area. In addition, RIF has been shown to be unstable in current media used in phenotypic drug susceptibility testing of SGM ( 27 , 28 ). RIF concentration in Middlebrook 7H9 medium had decreased by 92% after 7 days, and the microbiological assay revealed decreases in RIF concentration of ≥75% after 14 days ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wetzstein et al studied the efficacy of WGS in predicting M. abscessus resistance to macrolides and aminoglycosides. The results obtained by WGS were shown to be in full agreement with the Genotype NTM-DR line probe assay and phenotypic drug susceptibility testing [75]. Lipworth et al used sequencing data obtained from M. abscessus species for the identification of new mutations in erm and rrs genes potentially associated with macrolide antibiotic resistance.…”
Section: Wgs Perspectives For Diagnostics and Characterization Of Resistance Patterns Of Ntmmentioning
confidence: 68%